Analysis of Human Resource Development and Leadership Style on the Performance of Employees at the Wonogiri BKPSDM Office - Devi Triana; Zandra Dwanita Widodo; Atik Lusia (ProBisnis : Jurnal Manajemen, 2026)
Human resource management is nothing new in organizations, particularly in government institutions. Field observations show that equitable human resource development and the right leadership style can become a strength within an organization. The purpose of this study was to analyze the influence of human resource development and leadership style on employee performance at the Wonogiri BKPSDM Office through a qualitative approach. Qualitative research plays a crucial role in identifying social, cultural, and behavioral phenomena. In this study, the researchers used the Nvivo 14 application to assist in data analysis. This application helped process information obtained from interviews with informants. The Nvivo 14 visualization results show a strong correlation between human resource development and leadership style on the performance of BKPSDM Wonogiri employees. Thus, human resource development and leadership style play a significant role in sustainably improving BKPSDM Wonogiri employee performance.